(untitled) (Research, Society and Development, 2021)
The study aimed to demonstrate that plant species commonly used in folk medicine, released for use by ANVISA and described in the scientific literature, have great therapeutic potential and have not yet been fully explored. A survey was carried out in the Brazilian Pharmacopoeia – ANVISA. From this survey, three plant species were randomly selected: Achyrocline satureioides, Echinodorus grandiflorus and Schinus terebinthifolius. Soon after, a technological survey of them was carried out in order to identify possible patents related to plant species. After searching the databases, a total of 28 patents for the species A. satureioides, 22 patents for the species E. grandiflorus and 38 patents for the species S. terebinthifolius were found. After using the inclusion and exclusion criteria, there remained a total of 8 patents for the species A. satureioides, 8 patents for the species E. grandiflorus and 8 patents for the species S. terebinthifolius. The number of patent filings involving plant species studied in the service sector and/or products aimed at human health is still reduced, since all species are already described in the scientific literature, are in common use in popular medicine and are part of of the Brazilian Pharmacopoeia. Furthermore, not all uses described by folk medicine through ethnopharmacological studies are covered.